Descriptive and Time-Series Analysis of Rabies in Different Animal Species in Mexico - Ortega-Sánchez, Reyna; Bárcenas-Reyes, Isabel; Cantó-Alarcón, Germinal Jorge; Luna-Cozar, Jesús; E, Rojas-Anaya; Contreras-Magallanes, Yesenia G.; González-Ruiz, Sara; Cortez-García, Baltazar; Milián-Suazo, Feliciano (Frontiers in Veterinary Science, 2022)
The spatio-temporal epidemiology of rabies has related the influence of environmental factors and anthropogenic changes on the movements of the hematophagous bat Desmodus rotundus (D. rotundus). In Mexico, D. rotundus is the main transmitter of the rabies virus for different livestock species, modifying annually the fluctuation of the number of cases of rabies and its dissemination in subtropical areas and regions considered free. The purpose of this study was to perform a descriptive analysis of the distribution of cases of rabies in Mexico, and to perform a time series analysis to evaluate stationarity, and to predict the number of cases for the following year. A total of 3,469 of cases were reported in the period of interest, of which the 89.1% ocurred in cattle, 4.3% in horses, 1.5% in sheep, 0.6% in goats, 0.01% in pig, 3.1% in vampire bats, 0.3% in cervids, 0.2% in skunks, 0.1% in insectivorous bats, 0.1% in foxes, 0.1% in buffalous, 0.02% in coatis and 0.5% were not identified. The most frequent antigenic variants reported were AgV11, AgV5 and AgV3, associated with D. rotundus. The distribution of cases in bats correlates with the distribution of cases in domestic and wild animals; however, cases were observed in wild species in non-endemic areas of Mexico, like the State of Chihuahua where three cases were reported. The additive model used in the time series analysis showed a seasonal pattern with a peak of cases at the beginning of each year, from January to March. The model showed a good predicting value, the pearson correlation coefficient R2 was 0.705. The highest probability for the occurrence of rabies cases in the different species estimated by Ordinary Kriging, was in the coast of the Gulf of Mexico, involving the states of Tamaulipas, Veracruz, Tabasco, Chiapas and Yucatan. This study confirms that rabies in domestic and wild species is endemic in tropical and subtropical areas, however, cases have been observed in geographic areas previously free, and provides useful information to support actions to stop the spread of the rabies virus or the reservoir, and for planning vaccination strategies considering time and place.